The Most Difficult Vowel Sound Pronunciation among Three Different Semester Students at UIN Sunan Ampel Surabaya: An Acoustic Analysis - wulansari - (Tell : Teaching of English Language and Literature Journal, 2020)
Speaking language involves different skills like grammar, instruction, vocabulary and pronunciation. in contrast, the researcher only focuses on the students ‘errors on six English vowel quality: /ɪ/, /æ/, /ʌ/, /ɔ:/, /ʊ/, /ɜ:/ made by three different semesters at English Literature, UIN Sunan Ampel Surabaya based on the acoustic analysis. The purposes are to know the result of the formant frequencies, so it appears the percentage of the most difficult vowel. This research used descriptive qualitative method. The result of this research shows that the most difficult vowel or vowel error made by three different semesters are vowel /æ/, the total of incorrect vowel quality is 75. The average of the students made those errors was about 28.4%. Based on the data it conducted that the common source of student’s errors on vowels was because of voice happened, knowledge of pronunciation, phonetic symbols and habituation of speaking English.